Factors Affecting Expectancy for Character Growth in Online Games and Their Effect on Gamers' Loyalty - Izzuddin Alghifari; Rizal Edy Halim (Journal of Economics, Business, and Accountancy Ventura, 2019)
This study aims to understand the effect of expectancy for character growth (learning, novelty, escapism, enjoyment, social value, audio-visual value, and value for money) on online games towards online gamer loyalty. This quantitative research uses a purposive sampling method with a sample of 375 respondents. The data were processed using the Structural Equation Modeling (SEM) method. The results showed that learning, escapism, audio-visual value, and value for money have a positive effect on expectancy for character growth. However, novelty, enjoyment, and social value do not have an effect on expectancy for character growth. Furthermore, expectancy for character growth has a positive effect on online gamer loyalty. Therefore, game developers need to know the fantasy of gamers, improve the quality of graphics, and provide discounts to increase gamers’ loyalty